Mountain Graticules: Bridging Latitude, Longitude, Altitude, and Historicity to Biocultural Heritage - Fausto O. Sarmiento; Nobuko Inaba; Yoshihiko Iida; Masahito Yoshida (Geographies, 2022)
The interdependence of biological and cultural diversity is exemplified by the new conservation paradigm of biocultural heritage. We seek to clarify obsolescent notions of nature, whereby cultural construction and identity markers of mountain communities need to reflect localized, situated, and nuanced understanding about mountainscapes as they are developed, maintained, managed, and contested in spatiality and historicity. Using the nexus of socioecological theory, we question whether a convergent approach could bridge montological knowledge systems of either different equatorial and temperate latitudes, western and eastern longitudes, hills and snow-capped mountain altitudes, or hegemonic and indigenous historicity. Using extensive literature research, intensive reflection, field observation, and critical discourse analysis, we grapple with the Nagoya Protocol of the Convention of Biological Diversity (COP 10, 2010) to elucidate the benefit sharing and linkages of biocultural diversity in tropical and temperate mountain frameworks. The result is a trend of consilience for effective conservation of mountain socioecological systems that reaffirms the transdisciplinary transgression of local knowledge and scientific input to implement the effective strategy of biocultural heritage conservation after the UN Decade of Biological Diversity. By emphasizing regeneration of derelict mountain landscapes, invigorated by empowered local communities, promoted by the Aspen Declaration, the UN Decade of Ecological Restoration, and the UN International Year of Mountain Sustainable Development, montological work on sustainable, regenerative development for 2030 can be expected.